1985
DOI: 10.1139/z85-382
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and egg guarding by Atlantic wolffish (Anarhichas lupus: Anarhichidae) and ocean pout (Macrozoarces americanus: Zoarcidae) in Newfoundland waters

Abstract: 1985. Reproduction and egg guarding by Atlantic wolffish (Anarhichas lupus: Anarhichidae) and ocean pout (Macrozoarces americanus: Zoarcidae) in Newfoundland waters. Can. J. Zool. 63: 2565 -2568. The reproductive season, the sex that provides parental care, and the relationship of feeding with reproduction are reported for Atlantic wolffish and ocean pout in eastern Newfoundland. Both species move into shallow water in the spring, pair during the summer, and spawn in holes under and between boulders during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 10 publications
3
59
0
Order By: Relevance
“…Albikovskaya(1982) described the distribution and abundance of A. lupus by depth and temperature in the Newfoundland area, and Templeman (1984a) described migra_tions of the species from tagging in the same region. Keats et al (1985) observed reproduction and egg guarding by Atlantic wolffish during scuba-diving in coastal waters (5-15 m deep) of the eastern Avalon Peninsula, Newfoundland. Templeman (1984b) discussed the meristic variation in A. lupus from collections in most areas of the Northwest Atlantic (West Greenland to the Scotian Shelf).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Albikovskaya(1982) described the distribution and abundance of A. lupus by depth and temperature in the Newfoundland area, and Templeman (1984a) described migra_tions of the species from tagging in the same region. Keats et al (1985) observed reproduction and egg guarding by Atlantic wolffish during scuba-diving in coastal waters (5-15 m deep) of the eastern Avalon Peninsula, Newfoundland. Templeman (1984b) discussed the meristic variation in A. lupus from collections in most areas of the Northwest Atlantic (West Greenland to the Scotian Shelf).…”
Section: Introductionmentioning
confidence: 92%
“…Some eggs had reached their largest size (before clearing) as early as May-June, and it would not be surprising if some individuals spawned before September. Keats et al (1985), by scuba-diving in coastal waters along the eastern Avalon Peninsula, Newfoundland, found male and female Atlantic wolffish pairing during the summer and spawning in spaces under and between boulders during the autumn. It was common to find pairs in nesting spaces by August, and spawning occurred from late August to October.…”
Section: Spawning Periodmentioning
confidence: 98%
“…Several authors have further claimed that a low fecundity suggests parental care (Mead et al 1964, Breder andRosen 1966). A handful of direct observations of shallow-water species has confirmed that, in those species (e.g., Zoarces americanus; see also Table 1), burrows or other structures are used for housing the eggs, and these are often guarded (Gosztonyi 1977, Anderson 1984, Keats et al 1985, Silverberg et al 1987, Steimle et al 1999). Viviparity has evolved in some species (i.e., Z. viviparus and Z. elongatus [Koya et al 1995, Ojaveer and Jarv 2003, Tokranov 2005).…”
Section: Laboratory Observations Of Reproduction In the Deep-water Zomentioning
confidence: 99%
“…Many of these species have been observed guarding egg masses under rocks or kelp holdfasts (Gosztonyi 1977). In the Atlantic, species such as the ocean pout, Zoarces americanus, come into shallow water to set egg masses under boulders, which are also apparently guarded (Keats et al 1985, Steimle et al 1999. For deep-dwelling species, laboratory observations, such as those included here, are important for gathering additional information regarding the role of burrows because direct observation in the wild is difficult and opportunistic at best.…”
Section: Lycodapus Mandibularis Reproductive Behaviormentioning
confidence: 99%
“…a directed fishery for Atlantic wolffish; it is thought that they are typically solitary fish or, at most, paired during the spawning season (Scott and Scott, 1988;Le Francois et al, 2010), and it has been challenging to obtain large sample sizes for thorough biological analyses. To confound matters, these demersal fishes are often associated with complex habitat, such as rocky burrows and crevices (Keats et al, 1985), making them difficult to survey with trawl gear.…”
mentioning
confidence: 99%